The Development of Comics Based on Algebraic Literacy for 7th Grade Students of Junior High School - Azizah, Farida Nur; Cholily, Yus Mochamad; Cahyono, Hendarto (Study Program of Mathematics Education University of Muhammadiyah Malang, 2019)
This research aimed at describing the development process and the effectiveness of mathematics media using comics based on algebraic literacy for 7th-grade students of junior high school (SMP). The kind of research, that conducted, was Research and Development (R&D) by using the ADDIE model. In which the model was Analysis, Design, Development, Implementation, and Evaluation. The media was tested into 24 students of 7th-grade. The average result of the media validation test both the validators were 3,7 in which is categorized as very valid with a feasible description to be tested. While the average result of material validation was 3,39 which is categorized as very valid with a feasible description to be tested. The effectiveness analysis result obtained that the students gave very positive responses with the obtained percentages of 85,21% and the mastery percentages of the class were 87,5% ineffective category. Therefore, it can be concluded that the comics based on algebraic literacy is effective to be used in algebra material for 7th-grade students SMP.